The Old Phase of Javanese Villages as an Early Form of Participatory Democratic Governance in Indonesia - Kusumastuti, Kusumastuti (The ITB Journal Publisher, 2017)
Abstract. Indonesia has experienced seven developmental phases of the social system (ideology), i.e. (1) the old phase of Javanese villagesÂ (809 AD); (2) the kingdom era (1044-1886); (3) the colonial Dutch East Indies (1853 AD); (4) the Japanese occupation (1942-1945); (5) the settling period from 1945 to 1965; (6) the New Order (1965-1998); and (7) The Reform Era. This ideology affects the development system, which in turn affect the relationship between government and people, such as on the position, rights, and roles of the people in influencing and determining the direction, content and development priorities. Meanwhile, democracy as a political system will affect the development system. Likewise, the decision-making system for developments is strongly influenced by the political system. This paper aims to retrace the democracy in the social system of the âOld phase of Javanese Villages in Indonesia,â to understand and rediscover its values. Many Dutch and British officials admired and recognized these values as the most suitable social system for our nation. Unfortunately, after the kingdom age, the Dutch colonial era and later times, the concept of village democracy has been erased and replaced with a system that was more favorable for the ruling regime. Therefore, this study is expected to remind, enhance and complement the repertoire of knowledge that can be developed and can influence thinking to the enrich and improve democracy in the context of development, especially to build the concept of participatory planning as a medium of education and as a vision to unite the nation. The method used is literature study to discover and understand the historical situation. The village is chosen as a unit of study because it was the forerunner of the traditions and culture of community life as a reflection of the unity of thought and action that determine the direction, content, and priorities of collective action. The village is an entity on the smallest scale in the nation. The village is a âcellâ that forms an entity in the administration, law, and resources of the nation.Keywords. citizen participation, social system, system of government.Abstrak. Di Indonesia ada tujuh fase perkembangan sistem (ideologi) kemasyarakatan, yaitu (1) masa desa Jawa kunoÂ (809M); (2) masa kerajaan (1044-1886); (3) masa kolonial Hindia-Belanda (1853M); (4) masa pendudukan Jepang (1942-1945); (5) masa pengaturan tahun 1945-1965; (6) masa Orde Baru (1965-1998); dan (7) masa Reformasi. Ideologi itu kemudian mempengaruhi sistem pembangunan yang digunakan bangsa Indonesia karena ideologi mempengaruhi hubungan antara pemerintah dan rakyat. Misalnya pada bagaimana posisi, hak dan peran rakyat dalam mempengaruhi dan menentukan keputusan untuk memilih arah,Â isi dan prioritas pembangunan. Sementara itu, demokrasi sebagai suatu sistem politik akan mempengaruhi sistem pembangunan. Demikian juga dengan sistem pengambilan keputusan dalam pembangunan akan sangat dipengaruhi oleh sistem politik yang diterapkan. Tulisan ini bertujuan untuk membuka kembali demokrasi dalam sistem kemasyarakatanÂ padaâMasa Desa Jawa Kunoâ, dengan cara memahami dan menemukan kembali nilai-nilainya, yang oleh banyak petinggi dan pemikir bangsa Belanda dan Inggris dikagumi dan diakui paling cocok untuk bangsa kita. Sayangnya di masa kerajaan, Kolonial Belanda dan masa-masa selanjutnya, konsep demokrasi desa telah dihapus dan diganti dengan sistem yang lebih menguntungkan penguasa pada setiap rezim saat itu.Oleh karena itu, kajian ini diharapkan bisa mengingatkan, menambah dan melengkapi khasanah pengetahuan yang bisa dikembangkan dan mempengaruhi pemikiran bagi pengkayaan pengembangan demokrasi dalam pembangunan terutama untuk pengembangan konsep perencanaan partisipatif sebagai media edukasi dan mempersatukan visi bangsa. Metode yang digunakan adalah studi literatur, sebagai cara untuk menemukan dan memahami fakta-fakta di masa lalu. Sebagai unit kajian adalah desa karena desa merupakan cikal-bakal tumbuhnya tradisi dan budaya hidup bersama sebagai suatu cerminan kesatuan antara pemikiran dan tindakan yang menentukan arah, isi dan prioritas tindakan bersama sebagai entitas dalam skala terkecil bangsa. Desa sebagai âcellâ yang membentuk entitas dalam administrasi, hukum dan sumber-daya bangsa. Kata kunci. partisipasi warga, sistem kemasyarakatan, sistem pemerintahan.